The Influence of Local Taxes on the Local Own-Source Revenue of Bandung City During the Covid-19 Pandemic - Thomson, Thomson (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2023)
This research aims to determine the influence of local taxes on the Local Own-Source Revenue (Pendapatan Asli Daerah) of Bandung City during the Covid-19 pandemic. The population in this study consists of 216 data observations of the Local Own-Source Revenue of Bandung City for the years 2020 and 2021. The research method used in this study is descriptive and verification methods. The results indicate that the tax conditions of hotels, restaurants, entertainment venues, advertisements, parking, street lighting, groundwater, Land and Building Tax (Pajak Bumi dan Bangunan/PBB), Land and Building Acquisition Duty (Bea Perolehan Hak atas Tanah dan Bangunan/BPTHB), as well as the Local Own-Source Revenue of Bandung City during the Covid-19 pandemic have experienced changes in the increase of revenue and data processing. On average, the Local Own-Source Revenue of Bandung City has shown an increase in revenue compared to the period before the Covid-19 pandemic. DOI: https://doi.org/10.32897/ajib.2023.2.1.2910